THE MAGNETIC FIELD IMPACT ON ACCRETION RATE IN A PROTOPLANETARY DISK - Kuksa, M. M. (Одеські астрономічні публікації, 2012)
Recent observations are the evidence of a large-scale magnetic field in discs around classical T Tauri stars. A model of the axisymmetric thin protoplanetary disk in a global magnetic field is considered. A compressible magnetohydrodynamic set of equations is solved by using the explicit numerical method. The influence of a magnetic field and various turbulent kinematic and magnetic viscosity coefficients on the accretion rate in the disk is investigated.